Estimates of the Effectiveness for Urban Energy Conservation and Carbon Abatement Policies: The Case of Beijing City, China - Hu, Junmei; Liu, Gengyuan; Meng, Fanxin (Journal of Environmental Accounting and Management, 2026)
Cities play an important role in tackling climate change, as they consume close to 2/3 of the world’s energy and account for more than 70% of global greenhouse gas emissions. To assess the effectiveness of urban energy conservation and carbon mitigation measures, a detailed Long Range Energy Alternatives Planning (LEAP) model is developed and applied to simulate a series of emission reduction measures. The developed LEAP model is also aimed at analyzing how these emission reduction measures change energy consumption and carbon emission from 2016 to 2050. Fifty scenarios were defined to describe the future energy strategies in relation to the development of Beijing city, including a ‘Business as Usual’ scenario, 42 sub-scenarios, 4 sectoral compound scenarios and 3 system compound emission reduction scenarios. The ‘Business as Usual’ scenario assumes that the government will do nothing to influence the long-term trends of urban energy demand. The 42 sub-scenarios reflect the effectiveness of singular measure including clean energy substitution, terminal technological innovation, industrial structural adjustment in three energy demand sector as well as external input of power scenario in transformation sector. Each singular measure has three A, B, C three levels, which represent different intensity of the measure. Sectoral compound scenarios show the integrated effectiveness of B-level measures which reflects the strength of the existing policy in each sector. The final effectiveness of all energy conservation and carbon mitigation measures of assorted level are presented in 3 system compound emission reduction scenarios. A further analysis of decoupling relationship between energy consumption and economy under system compound scenarios is discussed.